A segregação residencial socioeconomica e sua relação com a desigualdade economica no Mexico - Medina Ortega, Marco Antonio; Benavides Rodríguez, Laura Elizabeth (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2018)
There exists a big diversity of perspectives in which the study of the city is tackled. In the last years there is observed an increasing interest in the works that analyze the city from the perspective of the social inequality and the urban segregation.In this document some contemporary reflections appear with regard to the topic of the socioeconomic residential segregation (SRS); the trip is realized from the first studies precedents on the segregation for the purpose of specifying a basic analytical frame, later to enter matter with the phenomenon of the segregation in Latin America, as well as to identify the relevancy studies and to specify the brief state of the question that will synthesize in the construction of two lines of the time one for Latin America and other one for Mexico. Nevertheless, our intention is that the present article is an opportunity to reflect on the differences and socioeconomic inequality; and concientizar the perception on other social groups who share with us the hierarchic socioeconomic pyramid